13. LATE WINDOW THROMBECTOMY OUTCOME OF PATIENTS WITH INTRACRANIAL ATHEROSCLEROSIS (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the modified Rankin scores (mRS) in patients with intracranial atherosclerotic cerebral infarction after mechanical thrombectomy performed within 6 hours of stroke onset.Methods: A prospective study on patients undergoing mechanical thrombectomy after 6 hours from onset, selected by DAWN/DEFUSE 3 criteria. Primary outcome: mRS at 90 days; secondary outcomes: functional independence rate (mRS 0-2), successful recanalization, and safety.Results: 162 patients were recruited including 88 presented with ICAS and 74 were non-ICAS (28 cardiac embolisms, 46 cryptogenic). ICAS patients had longer onset-to-groin times (18.0 [13.1-21.8] vs. 14.0 [13.5-18.0] hours, p = 0.007), smaller core (ADC < 620: 6.0 [1.5-15.0] vs.14.0 [4.0-25.0], p = 0.028) and lower hypoperfusion intensity ratio (0.22 [0.08-0.42] vs. 0.34 [0.19-0.49], p = 0.005). However, there was no difference in the mRS shift analysis (3 [2-4] vs. 3 [1-4], p = 0.74). Secondary outcomes showed significantly lower recanalization rates in the ICAS group (83% vs. 93%, p = 0.041), while no differences were observed for the proportion of patients with functional independence (48.9% vs. 43.2%, p = 0.46), parenchymal hematoma type 2 (4.55% vs. 1.35%, p = 0.38) or mortality rates (10.2% vs. 13.5%, p = 0.52).Conclusions: Compared to non-ICAS, ICAS patients had smaller infarct core, better collateral, and similar functional outcome, despite the longer symptom onset-to-groin, suggesting that the therapeutic time window may be extended in these patients.
Keywords: Stroke; intracranial atherosclerosis; mechanical thrombectomy; late window